Oxidative Stress Resistance in Metastatic Prostate Cancer: Renewal by Self-Eating - Balvan, Jan; Gumulec, Jaromir; Raudenska, Martina; Krizova, Aneta; Stepka, Petr; Babula, Petr; Kizek, Rene; Adam, Vojtech; Masarik, Michal (PloS one, 2015)
Resistant cancer phenotype is a key obstacle in the successful therapy of prostate cancer. The primary aim of our study was to explore resistance mechanisms in the advanced type of prostate cancer cells (PC-3) and to clarify the role of autophagy in these processes. We performed time-lapse experiment (48 hours) with ROS generating plumbagin by using multimodal holographic microscope. Furthermore, we also performed the flow-cytometric analysis and the qRT-PCR gene expression analysis at 12 selected time points. TEM and confocal microscopy were used to verify the results. We found out that autophagy (namely mitophagy) is an important resistance mechanism. The major ROS producing mitochondria were coated by an autophagic membrane derived from endoplasmic reticulum and degraded. According to our results, increasing ROS resistance may be also accompanied by increased average cell size and polyploidization, which seems to be key resistance mechanism when connected with an escape from senescence. Many different types of cell-cell interactions were recorded including entosis, vesicular transfer, eating of dead or dying cells, and engulfment and cannibalism of living cells. Entosis was disclosed as a possible mechanism of polyploidization and enabled the long-term survival of cancer cells. Significantly reduced cell motility was found after the plumbagin treatment. We also found an extensive induction of pluripotency genes expression (NANOG, SOX2, and POU5F1) at the time-point of 20 hours. We suppose, that overexpression of pluripotency genes in the portion of prostate tumour cell population exposed to ROS leads to higher developmental plasticity and capability to faster respond to changes in the extracellular environment that could ultimately lead to an alteration of cell fate.
Keywords: metastázy nádorů; autofagie; nádorové buněčné linie; Gene Expression Profiling; analýza hlavních komponent; průtoková cytometrie; Endoplasmic Reticulum; Cell Communication; endoplazmatické retikulum; Cell Self Renewal; reaktivní formy kyslíku; naftochinony; regulace genové exprese u nádorů; mitofagie; Entosis; Autophagy; mužské pohlaví; nádory prostaty; Naphthoquinones; Oxidative Stress; Cell Line, Tumor; Cell Size; velikost buňky; Flow Cytometry; Principal Component Analysis; Reactive Oxygen Species; Neoplasm Metastasis; Prostatic Neoplasms; časosběrné zobrazování; Humans; Gene Expression Regulation, Neoplastic; inhibiční koncentrace 50; buněčná sebeobnova; entóza; viabilita buněk; Cell Survival; Mitophagy; Inhibitory Concentration 50; stanovení celkové genové exprese; oxidační stres; mezibuněčná komunikace; Time-Lapse Imaging; lidé; Male